THE USE OF MULTI MEDIA IN LEARNING SKI IN HIGH ISLAMIC SCHOOL STATE TEBING TINGGI REGENCY - Sit, Masganti; Halimah, Siti; Sugiono, Sugiono (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
This research was conducted to determine the use of multi-media in learning Islamic Cultural History at the State Madrasah Aliyah Kota Tebing Tinggi. This research is located in Madrasah Aliyah Negeri (MAN), Tebing Tinggi City, which is located at Jalan Baja, Padang Hilir District, Tebing Tinggi City. The method approach used in this research is descriptive qualitative research. This type of qualitative descriptive research displays the results of the data as they are without the process of manipulation or treatment from others which is carried out using triangulation data collection techniques, namely through observation, interviews, and documentation studies.Â  From the results of this study, it can be concluded that the use of multi media in learning Islamic Cultural History in Tebing Tinggi City MAN has been applied to the SKI subject. The basis for using multi-media is based on the need to assist teachers in providing knowledge about Islamic Cultural History. The main objective and task of the teacher is to transfer knowledge (transfer of knowledge). The process of using multi-media is done by presenting the subject matter in the form of a slide on Microsoft Power Point. In addition to using media in the form of laptops, teachers also use additional media such as videos, pictures, speakers, the internet and other media assistance. The purpose of usin g multi media in learning Islamic Cultural History is to make it easier for teachers to deliver subject matter to students. The obstacles to the use of multi-media in learning Islamic Cultural History are limited to the selection and use of media types. Meanwhile, the opportunity for using multi media is that there are several learning media facilities that have been provided by the madrasah. The response to the use of multi media in learning Islamic Cultural History can be seen from the attention of students in seeing and listening to explanations from the teacher regarding the subject matter carried out in the classroom.